Factors influence job satisfaction among lecturers UiTM Jasin / Iskandar Ghani Ismail - Ismail, Iskandar Ghani (Faculty of Business and Management, 2014)
In order for UiTM to become a premier university with outstanding scholarship and academic excellence, the lecturer is the key towards reaching the vision of UiTM. A dedicated and committed lecturer will benefit UiTM in many ways especially in boosting the quality of teaching. The objective and scope of the study is to discover the factor influence the job satisfaction of lecturers in UiTM Jasin Campus. They are three influential factors that contribute the most toward job satisfaction, namely workload, remuneration and working environment. So from the study the researcher wants to know whether the workload, remuneration and working environment have the relationship or not in job satisfaction. The researcher needs to find a lot of reference for the literature review to support the data for this study. The researcher found the literature review from the references books, journals and also website. Then, literature is discussed about factor influence and job satisfaction that focusing on the relationship between them. The researcher have distribute to respondent that a lecturers UiTM Jasin. The result showed that workload, remuneration and working environment that was found to have significant positive relationship with job satisfaction.